Modern technoscience: mechanism of operation and organizational differences - Vityaz, Petr A.; Shcherbin, Vyacheslav K. (Journal of the Belarusian State University. Sociology, 2019)
The mechanism of contemporary technoscience operation that was being shaped in the course of interaction across such diverse academic disciplines within its framework as information and communication technologies, nanotechnology, artificial intelligence, biotechnology, social technologies, etc. is considered. The core organizational differences of modern technoscience versus traditional discipline-based science are analyzed. It justifies the conclusion that contemporary technoscience is a new developmental stage of global science.
Keywords: technoscience; information and communication technologies; nanotechnology; artificial intelligence; biotechnology; social technology